Control trial of porcine cysticercosis in Uganda using a combination of the TSOL18 vaccination and oxfendazole - Zachary Nsadha; Chris Rutebarika; Chrisostom Ayebazibwe; Bukenya Aloys; M. Mwanja; E. Jane Poole; Elizabeth Chesang; Angela Colston; Meritxell Donadeu; Marshall W. Lightowlers (BMC, 2021)
Abstract Background Neurocysticercosis caused by Taenia solium when the parasite lodges in the central nervous system, is an important cause of human seizures and mortality in sub-Saharan Africa. The parasite is prevalent in many regions of Uganda. Pigs are intermediate hosts for T. solium, and we evaluated a T. solium control program in pigs, involving vaccination of pigs with the TSOL18 vaccine and treatment with oxfendazole. Methods The study was conducted in two districts of Eastern Uganda involving the rural village communities of Bukedea (intervention area) and Kumi (control area) during 2016-2017. Seven hundred and thirty-four households were enrolled in the study. Pigs in the intervention area received intramuscular immunizations with TSOL18 (Cysvax™) and an oral medication with 30 mg/kg oxfendazole (Paranthic™) at approximately 3-monthly intervals for 18 months. Porcine cysticercosis was evaluated by post-mortem examination. At the beginning of the study, 111 pigs were examined. In an interim evaluation in the intervention area, 55 pigs were evaluated 12 months after starting the project. At the end of the study approximately 3 months after the final intervention, 55 pigs from the intervention area and 56 pigs from the control area were evaluated. Results The prevalence of porcine cysticercosis for the two sites was 16.2% at the beginning of the study (17.2% in the intervention area and 15.1% in the control area) with no statistically significant difference (P = 0.759) between the two study sites. Among the 110 animals assessed from the intervention site (55 at the interim evaluation and 55 at the final evaluation), no pig with viable T. solium cysts was found. There was a statistically significant difference between the prevalence at baseline (17.2%) and at the end of the study (0%) in the intervention area (P = 0.001) and a statistically significant difference between the intervention (0%) and control areas (5.4%) (P = 0.041) at the end of the study. Conclusions Three-monthly concurrent vaccination of pigs with the TSOL18 vaccine and medication with oxfendazole eliminated T. solium transmission by the animals involved in the study. Application of vaccination with medication in pigs has the potential to reduce transmission of T. solium in Uganda and other endemic countries.